Carbon-stabilized porous silicon biosensor for the ultrasensitive label-free electrochemical detection of bacterial RNA gene fragments - Grace Pei Chin; Keying Guo; Roshan Vasani; Nicolas H. Voelcker; Beatriz Prieto-Simón (Biosensors and Bioelectronics: X, 2024)
Herein, we report a carbon-stabilized porous silicon (pSi)-based electrochemical biosensing platform for the label- and amplification-free detection of bacterial 16S rRNA gene fragments that facilitates pan-bacterial detection. The sensing approach combines thermally carbonized pSi (THCpSi) structures as novel porous electrochemical transducers, and a highly sensitive sensing mechanism based on partial blockage of the pores caused by hybridization of 16S rRNA gene fragment to the DNA capture probe immobilized within the pores. Pore blockage upon RNA hybridization was quantified via differential pulse voltammetry as a decrease in the oxidation current of the redox pair ([Fe(CN)6]3/4−) added to the measuring solution. The use of carbon-stabilized pSi to build the biosensor has additional benefits: it favors high density of the immobilized bioreceptors and a large electroactive surface area, both further enhancing the overall sensitivity of the biosensor. The easily adjustable pSi morphology is key to design diagnostic tools fit-for-purpose. By tailoring the pore diameter, pore blockage upon analyte hybridization can be maximized, thus enhancing sensitivity. By tailoring film thickness, the surface area can be adjusted to optimize the amount of immobilized bioreceptors and the electroactive surface area. An excellent sensing performance was achieved by building the biosensor on THCpSi structures featuring a 27 nm pore diameter and a 1.6 μm film thickness, whose external surface was coated with a thin layer of silicon nitride (Si3N4), the latter contributing to maximize the pore blockage. The biosensor achieved a limit of detection of 2.3 pM when tested in 5% fetal bovine serum.